Parenting Management Strategies In Forming Learning Discipline Character In Children - Bernadetha Nadeak; Aden Sutiapermana; Izlan Sentryo; Intan Prastihastari Wijaya; Anik Lestariningrum (Jurnal Ilmu Sosial Mamangan, 2024)
This research discusses the role of parents and educators in shaping the character of children's learning discipline in the ever-changing digital and social era. Learning discipline is a vital skill that supports the development of independence, responsibility and consistency in learning. The focus of the research is parenting management strategies that are effective in shaping children's learning discipline character. Parents have a central role in children's character education, with parenting styles having a significant influence on learning discipline. This research aims to identify effective parenting management strategies, including implementing a regular study schedule, monitoring children's online activities, providing rewards and punishments, open discussions about education, modeling positive behavior, and rewarding children's achievements. Educators also play an important role through role models, positive habits, emphasizing responsibility, using rewards and recognition, developing goals and plans, encouraging reflection and self-evaluation, and providing support and assistance to students. The research method used is qualitative with a phenomenological approach. The research results highlight children's experiences in experiencing learning discipline and effective strategies in shaping their learning discipline character. With a better understanding of parental parenting styles and educators' strategies, it is hoped that we can help children face the challenges of learning in this modern era.